2016
DOI: 10.1016/j.trd.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the hidden potential of sugar beet industry brownfields (case study of the Czech Republic)

Abstract: Citation for final published version:Krejci, T., Dostal, I., Havlicek, M. and Martinat, Stanislav 2016. Exploring the hidden potential of sugar beet industry brownfields (case study of the Czech Republic). Transportation Research Part D: Transport and Environment 46 , pp. AbstractThe paper focuses on spatial analyses of sugar beet industry brownfields in the Czech Republic. In the first part of the paper history of sugar beet industry on the area of the Czech Republic is briefly presented, then links between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(14 reference statements)
0
6
0
1
Order By: Relevance
“…At the same time, however, it was confirmed that motivations for railway trespassing are subject to constant change in dynamically developing urban areas. Recent changes are influenced particularly by the restructuring of industry in the Czech Republic after 1989 that was followed by the emergence of brownfield and revitalization efforts [30,35]. Revitalization of brownfield sites in the urban environment and its impact on functional land use in proximity to railways are also the subject of studies in other European countries [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, however, it was confirmed that motivations for railway trespassing are subject to constant change in dynamically developing urban areas. Recent changes are influenced particularly by the restructuring of industry in the Czech Republic after 1989 that was followed by the emergence of brownfield and revitalization efforts [30,35]. Revitalization of brownfield sites in the urban environment and its impact on functional land use in proximity to railways are also the subject of studies in other European countries [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the development of settlement structures at railways and the emergence of trespassing is not commonly studied. More often, attention is given to issues of brownfield revitalization, where the relationships and links between the functional use of land and railway infrastructure are quite obvious, namely in towns [28][29][30].…”
Section: Situation In the Czechrepublicmentioning
confidence: 99%
“…Priskyrus teritoriją kaip AT, turi būti numatomi šie veiksmai siekiant subalansuoti miesto plėtrą pertvarkant jo teritorijas pagal darnios plėtros principus: − galutinės žemės paskirties parinkimas; − paskirties keitimo procedūros parinkimas (kokiu būdu turi būti pakeista teritorijos paskirtis); − tolesnio teritorijos naudojimo vizija, jos parinkimas, integravimo į bendrą urbanistinį karkasą strategija. Atsižvelgiant į mokslinėje literatūroje aptinkamus pavyzdžius (Paul Bardos et al 2016;Krejčí et al 2016), pramoninės paskirties objektų ir AT paskirties keitimas gali vykti keliais būdais: − kai paskirtis atnaujinama; − kai paskirtis keičiama išsaugant nepakitusią architektūrinę-urbanistinę išraišką. Tinka tuo atveju, kai objektas pripažintas industriniu paveldu; − kai paskirtis keičiama iš esmės keičiant situaciją -tai kompleksinė teritorijos regeneracija.…”
Section: Apleistų Teritorijų Vertinimo Principai Paskirties Keitimo Tipaiunclassified
“…The world-wide review study of kasraian et al (2016) does not comprise any paper from this region and even Seidenglanz's (2014) paper on current state of Czech and Slovak transport geography mentions this research agenda only marginally. The following topics can be mentioned in particular: the current processes of suburbanization (dostál et al 2010), changes in urban patterns of postmodern cities (krejčí et al 2016(krejčí et al , Mulíček et al 2016, integration into spatial and mobility planning (kortanová et al 2010(kortanová et al , Malasek et al 2011 or effects on regional development (kraft et al 2014(kraft et al , Michniak 2015.…”
Section: Introductionmentioning
confidence: 99%